2018
DOI: 10.1187/cbe.17-08-0190
|View full text |Cite
|
Sign up to set email alerts
|

Moving Evolution Education Forward: A Systematic Analysis of Literature to Identify Gaps in Collective Knowledge for Teaching

Abstract: A systematic analysis of the literature undertaken to identify gaps in collective knowledge for teaching undergraduate evolution is reported. A total of 316 peer-reviewed papers were analyzed to determine: evolutionary topics addressed; whether the focus was student thinking, assessment, instructional strategies, or goals; and the type of work. Future research priorities are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 47 publications
2
75
0
1
Order By: Relevance
“…Developers of scientific instruments need to clearly lay out under what conditions their assessment is to be used and to encourage those using the assessment outside of those parameters to gather more evidence. Ziadie and Andrews (2018) point out that any assessment should include the dimensions of the topic that are important to assess and include consistent methodology and interpretation of results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Developers of scientific instruments need to clearly lay out under what conditions their assessment is to be used and to encourage those using the assessment outside of those parameters to gather more evidence. Ziadie and Andrews (2018) point out that any assessment should include the dimensions of the topic that are important to assess and include consistent methodology and interpretation of results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Once data analysis is complete, the efficacy trial will enable us to explore new questions about the mediating factors that might influence the observed outcomes. It will contribute to knowledge of the critical components of effective instruction in evolution (Ziadie and Andrews 2018), which is a gap in educational research. In the meantime, educators can use the free Evolution: DNA and the Unity of Life curriculum with confidence in the materials' feasibility and educational value.…”
Section: Discussionmentioning
confidence: 99%
“…First, the current concept inventories cover only a few of the major topics that may be taught in an undergraduate evolution course. In an analysis of peer-reviewed evolution education research, Ziadie and Andrews (2018) found that the majority of published papers pertaining to assessment of evolutionary concepts relate only to natural selection or phylogenetics (particularly tree-thinking). Many common topics in undergraduate evolution courses had limited or no coverage.…”
Section: Introductionmentioning
confidence: 99%